2020
DOI: 10.1007/s00402-020-03537-w
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative psychological distress no reason to delay total knee arthroplasty: a register-based prospective cohort study of 458 patients

Abstract: Introduction Total knee arthroplasty (TKA) is effective in alleviating pain and improving function in patients with knee arthritis. Psychological factors are known to affect patient satisfaction after TKA. It is important to determine the effectiveness of TKA in patients with presurgical anxiety and/or depression to avoid excluding them from surgery. Materials and methods A prospective cohort study was conducted on all patients who underwent TKA during 2016–2018. Patients were divided into four groups: with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…A recent meta-analysis concludes that OA patients should be screened for anxiety and depression for better pain management and to increase clinical awareness around the association between psychological aspects and persistent pain [ 46 ]. However, eligibility for surgery should not be influenced by preoperative anxiety or depression symptoms [ 47 , 48 ]. In addition, OARSI guidelines suggest that patients’ clinical status may improve before surgery if they are contacted regularly by phone [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis concludes that OA patients should be screened for anxiety and depression for better pain management and to increase clinical awareness around the association between psychological aspects and persistent pain [ 46 ]. However, eligibility for surgery should not be influenced by preoperative anxiety or depression symptoms [ 47 , 48 ]. In addition, OARSI guidelines suggest that patients’ clinical status may improve before surgery if they are contacted regularly by phone [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the indication for surgery for UNE should be very clear and sometimes strict. An interesting question is if patients with preoperative anxiety and/or depression benefit from a specific type of surgery, but data indicate that patients, surgically treated with a total knee arthroplasty, are improved regardless of their presurgical psychological status [30]. Preoperative information, where also assessment of the psychological and psychiatric status is considered before surgery, seems to be crucial [31] and anxiety and depression symptoms may also decrease after a total knee arthroplasty [32].…”
Section: Discussionmentioning
confidence: 99%
“…The full text of each article was reviewed, 21 of which fulfilled our inclusion criteria. Most full-text screened articles that were excluded did not use clinical diagnoses to verify the presence of a psychiatric disorder [1-4, 6, 8, 10, 16, 19, 21, 23-25, 29-43, 46, 52, 56, 58, 61, 62, 64, 66, 67, 72, 76, 80, 85-89, 92, 93]. A review of each study’s reference list did not yield any additional articles (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Studies evaluating the association between psychiatric illness and orthopaedic surgical outcomes have yielded mixed results. This may be partly explained by variations in how psychiatric illness is identified, with some studies using preoperative surveys and others ensuring that appropriate clinical diagnostic criteria have been met among studied patient populations [8,21,37,52,70,76]. Although some studies have reported worse perioperative outcomes among patients with diagnosed psychiatric illnesses [45,48,73,83,84], other research suggests these patients have a lower risk of complications, shorter lengths of stay (LOS), and higher costs of care than patients without a psychiatric illness [11,59,78].…”
Section: Introductionmentioning
confidence: 99%